Introduction to time-limited group psychotherapy - MacKenzie, K. Roy. (Washington, DC : American Psychiatric Press, 1990)
Introduction to Time-Limited Group Psychotherapy is a basic text designed for the clinician who already has experience in individual psychotherapy. However, the breadth of perspective and discussion of therapeutic strategies should be of value to the more experienced psychotherapist as well.
Includes index and bibliographical references.
Keywords: Brief psychotherapy; Group psychotherapy; Psychotherapy, Brief; Psychotherapy, Group